2016
DOI: 10.1016/j.triboint.2015.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Roughness and wettability of surfaces in boundary lubricated scuffing wear

Abstract: The diversity of multidisciplinary approaches suggests that fundamentals of scuffing require systemic, complex multi-scale and multi-physics analysis of an irreversible process as it is postulated in present study. That is probably one of the reasons of lack of unequivocal model of this irreversible transitional process from stable more or less lubricated wear to scuffing described only by one or few authors in equation(s) form. Therefore, it is useful to characterize the tribological surface properties in fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…Simultaneously, these researchers paid attention to the fact that when a surface is too rough, it also tends to generate high wear due to the high true contact stresses on the peaks of the asperities. These statements are confirmed by Wojciechowski et al [18] and Kubiak et al [19], who found that surfaces with a higher Kr parameter have better wettability properties in terms of oil spreading on such surfaces, and lower contact angles due to the spreading dynamics of the oil. Kr determines the mean slope of roughness motifs, which according to the ISO 12085 standard can be determined as a portion of the primary profile between the highest points of two local peaks of the profile, which are not necessarily adjacent.…”
Section: Introductionsupporting
confidence: 53%
“…Simultaneously, these researchers paid attention to the fact that when a surface is too rough, it also tends to generate high wear due to the high true contact stresses on the peaks of the asperities. These statements are confirmed by Wojciechowski et al [18] and Kubiak et al [19], who found that surfaces with a higher Kr parameter have better wettability properties in terms of oil spreading on such surfaces, and lower contact angles due to the spreading dynamics of the oil. Kr determines the mean slope of roughness motifs, which according to the ISO 12085 standard can be determined as a portion of the primary profile between the highest points of two local peaks of the profile, which are not necessarily adjacent.…”
Section: Introductionsupporting
confidence: 53%
“…Figure 5d). These effects are beneficial, especially in extreme pressure conditions, whence the lubricants can easily be squeezed out from the contact at the surfaces with lower wettability, lowering the resistance to scuffing [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The wetting properties of solid surfaces are affected by both their intrinsic chemical composition and by their morphology [8]; for example hydrophobic surfaces roughened on purpose can become super hydrophobic, showing an efficient mechanism of selfcleaning [9].…”
mentioning
confidence: 99%